The Eloquence of the Speech Act in the Political Discourse )The Discourse of the Resistance Political Media between 2006-2011 as an example) - Basal, Mohammad; Saied, Ferias (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The Eloquence in the speech concept has no longer been just an esthetic study of the phrase or the full understanding of its esthetic aspects.Moreover ,it is the full understaning of the eloquentic element in its context ;that is why we find that all the modern linguistists study the discourse -regardless to its type-starting from the speech acts which are responsible for changing the speeches to actswith a social character .Furthermore,the speech is not only an information exchange ,but also acts representing in the real life according to a set of rules that can change the situation of the receiver and organise his believes and behaviour.Finally ,in a world full of signs and semantic speeches which their senders try to acquirethe receiver,we notice that the political media discourse has a basic role in specifing the receiver's behaviours in a way or another.